An Actantial and Functional Structure Analysis on Mildred Taylor’s Roll of Thunder Hear My Cry: Analisis Struktur Aktansial dan Fungsional pada Mildred Taylor's Roll of Thunder Hear My Cry - Santoso, Heri Dwi (JEES (Journal of English Educators Society), 2017)
To a certain extent, a structural study is good enough to comprehend the very substance of a literary work. Given the above thesis, the researcher attempted to conduct a structural research on Roll of Thunder Hear My Cry (ROTHMC), an African-American novel, using actantial and functional structure analysis. This study aimed at comprehending the basic framework of the story that leads to the revelation of the plot and relations between characters, which indicated the African-American protagonist’s struggle to challenge white supremacy. Method used in the research was descriptive qualitative. Results found that the protagonist was David Logan, an African-American independent farmer that had an ambition to free African-American community from white people’s repressions. It was also found that the ambition and dream of David Logan about African-American freedom and independence and his awareness on the repression toward African-American people (Sender) has made him struggled to make African-American or African-American become a free race with dignity in the United States, where land and other things at the time was dominated by White people. Meanwhile, the functional analysis showed the plot structure of ROTHMC, which was centered on the struggles of David Logan and the family to challenge white supremacy.